Ecology of Intertidal Rocky Shores Related to Examples of Coastal Geology across Phanerozoic Time - Johnson, Markes E. (Journal of marine science and engineering, 2024)
The boundary between land and sea is among the most extensive and extreme ecological barriers on planet Earth. Intertidal organisms living at this junction are subject to potentially lethal conditions related to desiccation, temperature fluctuations, and wave shock. Although difficult to quantify at a global level, rocky coasts account for between a third and three-quarters of all shorelines today. Resistant to coastal erosion, rocky coasts also exhibit adaptations by marine invertebrates and marine algae within intertidal zones that are geographically widespread. Biotic composition is variable depending on the tidal range at any given place and on climatic differences between tropical and more temperate latitudes. Contemporary granite shores having low recession rates with well-established biotic zones are reviewed in three regions: Mount Desert Island in Maine, USA (44° N latitude), Mahé and Praslin islands in Seychelles (4°30′ S Latitude), and Lizard Island off the coast of Queensland, Australia (14°40′ S Latitude). The zonal composition and overall biotic diversity at these locations are compared, as well as the fossilization potential of key biota. Over the Phanerozoic time period during the last 538 million years, the ratio between land and ocean varied as a function of plate tectonics depending on the maximum dispersal or coalescence of continents and on relative changes in global sea level. Fossil biotas from a dozen paleoislands with dominant rocky shores that range from 485 million to 125,000 years in age are reviewed to show diversification through time, taking into account episodic mass extinctions. Relationships between storm tracks and volcanic eruptions that factor into physical disruptions are also considered as means of rapid burial and preservation. Themes related to rocky-shore ecology and paleoecology benefit from the cross-fertilization of ideas by marine biologists and marine paleontologists. It is hoped this review may attract a cohort of new students to these allied fields of study, especially in Asia, Africa, and South America.